Looks can be deceiving: recently published Bacopa llanorum (Plantaginaceae) is synonymous with Lindernia brachyphylla (Linderniaceae) and B. debilis is an unnecessary combination - Scatigna, André Vito (Phytotaxa, 2023)
Important efforts toward exploring the flora of the Orinoquia region of Colombia and Venezuela resulted in several novelties, including the recently described Bacopa llanorum. Here I present a reinterpretation of the identity of this species and place it under the synonymy of Lindernia brachyphylla. Additionally, I make a remark on the status of the combination Bacopa debilis and propose a second step lectotypification for Herpestis reptans. The content of this contribution highlights the importance of specimen exchange between megadiverse countries and the crucial role of taxon experts in peer review of papers describing new species.